Sex-specific colonic mitochondrial dysfunction in the indomethacin-induced rat model of inflammatory bowel disease - Hoang, Ngoc; Brooks, Karen; Edwards, Kristin (Frontiers in Physiology, 2024)
Introduction: Inflammatory bowel disease (IBD) is characterized by chronic inflammation of the gastrointestinal tract and encompasses Crohn’s Disease and Ulcerative Colitis. Women appear to have more severe and recurring symptoms of IBD compared to men, most likely due to hormonal fluctuations. Studies have shown that mitochondrial dysfunction plays a role in the development of inflammation and there is evidence of colon mitochondrial alterations in IBD models and patients. In this study we have identified the presence of sex-specific colon mitochondrial dysfunction in a rat model of IBD. Methods: Eight-week-old male and female rats were treated with indomethacin to induce IBD and mitoTEMPO was administered daily either after or before induction of IBD and until euthanasia. Colons were collected for histology and mitochondrial experiments. Intact mitochondrial respiration, reactive oxygen species (mtROS), the activities of the individual electron transport complexes and the activities of the antioxidant enzymes were measured to assess mitochondrial function. Results: IBD male rats showed a decrease in citrate synthase activity, cardiolipin levels, catalase activity and an increase in mtROS production. IBD females show a decrease in intact colon mitochondrial respiration, colon mitochondria respiratory control ratio (RCR), complex I activity, complex IV activity, and an increase in mtROS. Interestingly, control females showed a significantly higher rate of complex I and II-driven intact mitochondrial respiration, MCFA oxidation, complex II activity, complex III activity, and complex IV activity compared to control males. The use of a mitochondrial-targeted therapy, mitoTEMPO, improved the disease and colon mitochondrial function in female IBD rats. However, in the males there was no observed improvement, likely due to the decrease in catalase activity. Conclusions: Our study provides a better understanding of the role mitochondria in the development of IBD and highlights sex differences in colon mitochondrial function. It also opens an avenue for the development of strategies to re-establish normal mitochondrial function that could provide more options for preventive and therapeutic interventions for IBD.